Metody detekce a charakterizace Cympylobacter sp - Hochel, Igor (Chemické listy, 2009)
Campylobacters are ubiquitous microorganisms responsible for infections in humans and animals. The enteritis caused by these bacteria is characterized by diarrhoea, fever and abdominal pain. Although it is usually a self-limiting disease that does not require antimicrobial therapy, the infection can lead, though rarely, to serious sequelae such as reactive arthritis and the Guillain-Barré syndrome. The pathogens are frequently found in the environment and in many foods of both animal and plant origin. This review is focused on recent methods used for isolation, identification and characterization of clinically important Campylobacter species.
Keywords: Serotyping; Polymerase Chain Reaction; Campylobacter Infections; kampylobakterové infekce; reagenční diagnostické soupravy; Reagent Kits, Diagnostic; financování organizované; imunochemie; Molecular Diagnostic Techniques; Bacteriological Techniques; Campylobacter; Financing, Organized; Immunochemistry; diagnostické techniky molekulární; bakteriologické techniky; polymerázová řetězová reakce; sérotypizace